ANALISIS PENGARUH KINERJA KEUANGAN PEMERINTAH KABUPATEN DAN KOTA TERHADAP INVESTASI, DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI JAWA TIMUR (Studi Komparatif Tentang Kinerja Keuangan Pemerintah Kabupaten Dan Kota Periode Tahun 2001-2005) - IKA, ALIADI (Program Doktor Ilmu Ekonomi, 2009)
This research is ratio analysis APBD modeling by comparing / attainment result of comparability (outcome) every periodisation of exercise of APBD the Government of regency and the Government of city in East Java, so that trends of standard performance knowable of its the area and influence to Invests and Gross Regional Domestic Product (PDRB). Step research and Process result of analysis and statistic model SPSS of 12 for windows solution based calculation discriminant analysis, of financial performance analysis 38 (thirty eight) the Government of regency and the Government of city in East Java in time line the year 2001-2005 obtained result that from in general covering growth APBD, Independency, Effectivity, Routine Expenditure activity and development expenditure activity, what has good standard performance there is fourth the Government of regency and the Government of city. Parsial Least Square (PLS) express, hence growth of Invests does have an effect on doesn’t have significant influence to growth PDRB, this thing is caused by the investment data is acceptance data / recommendation of appproved Domestic Investment (PMDN) and approved Foreign Investment data (PMA), mean investment recommended has not entirely having operational or is not able yet to realized by some things, for example delaying it investors enthusiasm to inculcate its the legal capital in East Java, so well as invesment of capital with the low labour absorbtion, so Investment contribution has not given positive impact to earnings of public or multiplier effect investment has not been realized so that investment to PDRB declines / decreases.Key word : Financial performance, Investment,Gross Regional Domestic Product